ANALYSIS OF FINTECH PEER-TO-PEER (P2P) LENDING APPLICATIONS IN IMPROVING FINANCING ACCESS FOR MSMEs IN INDONESIA - Lilis Karlina; Muhammad Fauzan (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
This study aims to analyze the role of peer-to-peer (P2P) lending fintech applications in improving access to financing for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using qualitative methods, this study explores several leading fintech applications, including Modalku, Kredivo, Akseleran, and ALAMI Funding Syariah. The results show that these applications provide fast, easy, and transparent financing alternatives for MSMEs that often experience difficulties in obtaining capital from traditional financial institutions. Furthermore, this study identifies differences in business models, market segments, and the benefits and risks faced by users and investors. These findings are expected to provide insights for stakeholders, including the government, industry players, and the public, in efforts to increase financial inclusion in Indonesia. With a better understanding of P2P lending applications, it is hoped that a more inclusive and sustainable financial ecosystem can be created, contributing to national economic growth.